Quality, Readability, and Accessibility of Online Content From a Google Search of "Macular Degeneration": Critical Analysis. (November 2022) - Hua, Hong-Uyen; Rayess, Nadim; Li, Angela S.; Do, Diana; Rahimy, Ehsan
Purpose: This work aims to assess the quality, accountability, readability, accessibility, and presence of Spanish translation in online material through a Google search of "macular degeneration". Methods: In this retrospective cross-sectional analysis of website results from a Google search of "macular degeneration", the quality and accountability for each website were assessed using the DISCERN criteria and the Health on the Net Foundation Code of Conduct (HONcode) principles. All 31 sites were independently graded by 2 ophthalmologists. Readability was evaluated using an online tool. The presence of accessibility features on the website and Spanish translation was recorded. The primary outcome measure was the DISCERN and HONcode quality and accountability scores of each website. Secondary outcome measures included the readability, accessibility, and presence of Spanish translation. Results: The mean ± SD of each criterion across all 15 DISCERN questions was 2.761 ± 0.666 (out of 5). The mean HONcode score for all websites was 7.355 ± 3.123. The mean consensus reading grade level was 10.258 ± 2.49. There were no statistically significant differences in any score between the top 5 websites and the bottom 26 websites evaluated. Accessibility was available on 10 of 31 websites. Spanish translation was available on 10 of 31 websites. Conclusions: The top 5 websites that appeared on a Google search did not have better quality or readability of online content. Improving quality, accountability, and readability can help improve patients' health literacy regarding macular degeneration.